Alteration of hyperpolarization-activated cation current-mediated metaplasticity contributes to electroconvulsive shock-induced learning and memory impairment in depressed rats - Ren, Li; Yu, Jian; Chen, Hengsheng; Luo, Jie; Lv, Feng; Min, Su (Frontiers in Psychiatry, 2024)
Background Accompanied by a rapid and effective antidepressant effect, electroconvulsive shock (ECS) can also induce learning and memory impairment. Our previous research reported that metaplasticity is involved in this process. However, the mechanisms still remain unclear. This study investigated the role of Ih current in the metaplastic changes and learning and memory impairment induced by ECS in depressive rats. Methods Depressive rats received ECS after modelling using chronic unpredictable. ZD7288, a type of Ih current inhibitor was used to verify the effect of Ih current. The sucrose preference test and Morris water maze were used for behavior testing. Changes in metaplasticity was assessed with the LTD/LTP threshold by stimulation at different frequencies. Spontaneous and evoked action potentials (APs) were measured to confirm difference of neuronal excitability. Additionally, the amplitude of Ih current was analyzed. Results ECS exerts antidepressant effect, but also induce spatial learning and memory dysfunction. ECS up-regulates the LTD/LTP threshold. In rats treated with ECS, the frequency of spontaneous and evoked APs is significantly reduced. In addition, ECS induces changes in the intrinsic properties of AP, including a decrease of AP-half width and peak amplitude, and an increase in AP time to peak and post-hyperpolarization potential amplitude. In particular, ECS increases both instantaneous and steady-state Ih currents. However, Inhibition of Ih current with ZD7288 results in a relief of learning and memory impairment and a decrease in threshold, as well as a significant reversal of whole-cell electrophysiological changes. Conclusion ECS-induced learning and memory impairment is caused by neuronal hypoexcitability mediated metaplasticity, and upregulation of LTD/LTP threshold by an increase in Ih current.